T. S. Eliot, rhizome and network concepts: Innovations in modernist and post-modernist poetry - Shcherbak, Nina F. (Вестник Томского государственного университета)
This research aims to show the importance of the paradigm change. Taking in account the notion of the episteme introduced by Michel Foucault, I look at patterns that are developed by contemporary art critics and writers. The article discusses the concept of rhizome as related to network concepts through the process of revealing innovations in modernist and post-modernist poetry (the example chosen is the poetry by T.S. Eliot). Rhizome and network concepts are directly related to a contemporary view of the state-of-the art paradigm associated with cultural and social development. It is often viewed as applicable to the study of literary texts. The chosen methodology includes the structural semantic study of literary texts and the analysis of the views on the innovations in modernist and post-modernist poetry. The results of the research allow hypothesizing that postmodern philosophy is directly applicable to the study of modernist (as well as post-modernist and contemporary literary texts) if not social processes. One of the possible examples could be seen in the development of a poetic paradigm with modernist (and post-modernist) writing which uses language as a medium, when a poem becomes a means of expressing the transcendental and actualizing the network concept. The poetry by Eliot is an example of innovations that the poet was undertaking. His theory of the objective correlate, attention to language, echo-elements is in accordance with contemporary poetic and prosaic innovations. Initially Eliot was opposing the principles outlined by Romantic poets. His attention to language and metaphysics allowed foreseeing post-modern tendencies in the development of literary texts. Post-modernism is characterized by a change of the aesthetic pattern. Anti-narrative practices, the concept of silence, attention to minor details, rhythm, intonation patterns are characteristics of the modern text. Contemporary writers, art critics, musicians introduce such concepts as accumulation, multiplication, small bang, genetic transformation, the so-called "shapes with windows" concept. These are the techniques that were explicitly or implicitly used by Eliot and his followers at the beginning of the era of innovation. Meta-modernist techniques like the concepts "oscillation" and "compression" allow hypothesizing that language innovations undertaken by Eliot show the contemporary paradigm patterns as well. Rhizome and network concepts allow one to see common patterns of development and innovation of poetic, literary, cultural, and philosophic scenes; characteristics of the contemporary aesthetic era.